BUILDING COMMUNICATION BETWEEN FAMILY MEMBERS AS A FORT OF FAMILY RESILIENCE - Ariansyah, Jeri (Universitas Islam Negeri Raden Fatah Palembang, 2021)
This paper discusses about building communication between family members as a fortress of family resilience. The family is the basis for maintaining diversity, the family is very important to maintain the social understanding of family. As social beings, humans are never separated from communication. Communication is often a fundamental problem in one's family household relations, especially what often becomes a conflict is communication between husband and wife who lacks understanding of the concept of communication patterns in the family in order to maintain family resilience in the household. The purpose of this paper is to provide and express the concepts and principles of communication in the family so that it can be a solution on how to build communication in the family that can fortify family resilience. As for the focus in this paper is how the concept of communication patterns, communication as an ethical value to realize family resilience, communication as the realization of ma'ruf relationships in the family, the theory of ethical values ​​and their relevance to the family communication system and the concept of family resilience. This paper is included in the type of normative legal research literature (library research). By using a conceptual approach and a statutory approach. the type of data in this study using qualitative data. The results of this paper conclude that family resilience is very influential on the concept of communication in the family. By understanding the concepts and principles of communication patterns between family members, they can maintain resilience and strength in the family, so that they can realize the purpose of marriage, namely forming a sakinah, mawaddah and rahmah family as contained in the Qur'an Surah Ar-Rum verse 21. Keywords: communication, family resilience, social